Assessment of planetary protection requirements for Mars sample return missions (National Academies Press, 2009)
NASA maintains a planetary protection policy to avoid the forward biological contamination of other worlds by terrestrial organisms, and back biological contamination of Earth from the return of extraterrestrial materials by spaceflight missions. Forward-contamination issues related to Mars missions were addressed in a 2006 National Research Council (NRC) book, Preventing the Forward Contamination of Mars. However, it has been more than 10 years since back-contamination issues were last examined. Driven by a renewed interest in Mars sample return missions, this book reviews, updates, and replaces the planetary protection conclusions and recommendations contained in the NRC's 1997 report Mars Sample Return: Issues and Recommendations. The specific issues addressed in this book include the following: the potential for living entities to be included in samples returned from Mars; scientific investigations that should be conducted to reduce uncertainty in the above assessment; the potential for large-scale effects on Earth's environment by any returned entity released to the environment; criteria for intentional sample release, taking note of current and anticipated regulatory frameworks; and the status of technological measures that could be taken on a mission to prevent the inadvertent release of a returned sample into Earth's biosphere.